THEME AND RHEME IN “PEPONGOTEN” AT GAYO WEDDING CEREMONY - Khairiah Ariady; Sumarsih Sumarsih (State University of Medan, 2014)
ABSTRACT This study deals with theme in “pepongoten” at Gayo wedding ceremony. The data were taken from informants and tape recorded of the Gayo wedding ceremony which was taken directly from SebukuInenMayak and Sebukuine in Pepongoten. Besides, some books of Gayowedding ceremony were used to complete the data. The method of the research was qualitative descriptive. It gives description about the theme used in Pepongotenat Gayowedding ceremony. The analysis of this research was data collection, data reduction, data display and at last data verification. The findings show that there were three types of theme used in Pepongoten, they are Textual, Topical, and Interpersonal. Those types of Theme and functions of theme reflected Gayonese cultural values namely politeness, respect to the elder, friendly and resoluteness value. These findings imply the importance of honoring parents in every aspect of life. Keywords:theme used, Linguistics, Descriptive Qualitative Design